2016
DOI: 10.1590/1413-82712016210106
|View full text |Cite
|
Sign up to set email alerts
|

Mediação no Zulliger: Evidências de Validade em Amostra de Não Pacientes

Abstract: ResumoConsiderando a influência de elementos culturais na avaliação da personalidade e a diversidade destes no cenário brasileiro, buscou-se verificar a validade do Zulliger em uma amostra gaúcha de não pacientes, focalizando as variáveis de mediação. Participaram 40 indivíduos, com idades entre 18 e 43 anos, de ambos os gêneros, escolaridade de ensino médio, do interior do Rio Grande do Sul. Foram feitas análises estatísticas descritivas e comparativas entre o grupo gaúcho e os dados normativos brasileiros. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(54 reference statements)
1
4
0
1
Order By: Relevance
“…Finally, by responding to the proposed objective, this study evidenced the importance of using the Zulliger to assess elderly in HD, which enhances the power of the tool and strengthens the use of the Comprehensive System, supporting earlier studies (Grazziotin & Scortegagna, 2016;. Among the results: (a) elderly with CKD present decreased productivity, cognitive problems and impaired interpersonal relationship when compared to the NCG; (b) significant differences were verified between the cognitive (Xu%, X-%, R) and interpersonal relationship processes (Fd, Isolation, GHR:PHR) in the CG when compared to the NCG.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, by responding to the proposed objective, this study evidenced the importance of using the Zulliger to assess elderly in HD, which enhances the power of the tool and strengthens the use of the Comprehensive System, supporting earlier studies (Grazziotin & Scortegagna, 2016;. Among the results: (a) elderly with CKD present decreased productivity, cognitive problems and impaired interpersonal relationship when compared to the NCG; (b) significant differences were verified between the cognitive (Xu%, X-%, R) and interpersonal relationship processes (Fd, Isolation, GHR:PHR) in the CG when compared to the NCG.…”
Section: Discussionsupporting
confidence: 80%
“…O fato da maioria das pesquisas com o ZSC buscar por qualidades psicométricas (Pasquali, 2010;Miguel, 2017) contribui para os avanços do método, em especial, ao verificar o interesse de buscar evidências de validade para diferentes faixas etárias e contextos. Nota-se que das pesquisas conduzidas uma indicou boa precisão temporal , três indicaram boas evidências de validade para uso no contexto organizacional (Ferreira & Villemor¬Amaral, 2005;Grazziotin & Scortegagna, 2012;Grazziotin & Scortegagna, 2013), quatro para uso com crianças (Villemor-Amaral & Quirino, 2013;Tavella & Villemor-Amaral, 2014;Villemor-Amaral & Vieira, 2016) e os demais avaliaram a validade de alguns indicadores do instrumento (Villemor-Amaral & Machado, 2011;Franco & Villemor-Amaral, 2012;Franco & Villemor-Amaral, 2012b;Villemor-Amaral & Cardoso, 2012;Grazziotin & Scortegagna, 2016;Gregoleti & Scortegagna, 2017).…”
Section: Discussionunclassified
“…Some studies have demonstrated the contributions of the ZSC and the limitations of its use in the personality assessment, both at the international level (Aguilar & Graso, 2015;Carpio & Lugón, 2011;Contreras-Milián, González-Pérez, & Herrera-Espinosa, 2016) as well as in the Brazilian context (Cardoso, Gomes, Pacheco, & Viana, 2018;Grazziotin & Scortegagna, 2016a;2016b;Gregoletti & Scortegagna, 2017;Miguel, Zuanazzi, & Villemor-Amaral, 2017;Rien, Scortegagna, Grazziotin, & Bertolin, 2017). However, studies that address cognition in healthy adults (Grazziotin & Scortegagna, 2016a; and those that include older and long-lived adults are rare (Aguilar & Graso, 2015;Grazziotin & Scortegagna, 2018). Aguilar and Graso (2015) evaluated the cognitive functioning of elderly and long-lived adults using ZSC and neuropsychological instruments (MMSE, clocks test).…”
mentioning
confidence: 99%
“…Some investigations have sought to evidence the validity of ZSC by analyzing the influence of cultural elements on cognitive and personality assessment. Considering Brazilian cultural diversity, Grazziotin and Scortegagna (2016a) sought the validity of ZSC to evaluate information identification/translation processes, mediation variables, with samples of healthy adults from different Brazilian states. A total of individuals of both genders participated, with ages varying between 18 and 43 years (M = 26.50) and all of them with high school education level, in the state of Rio Grande do Sul.…”
mentioning
confidence: 99%